Efficacy of Unripe Papaya (Carica papaya L.) Consumption on Breast Milk Production Among Lactating Women - Hana Fitria Andayani; Dini Afriani; Citra Mira Kania Nurjanah; Gita Arisara (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Breast milk is the main source of nutrition for infants during the first six months of life, yet evidence on accessible, food-based ways to support milk production in Indonesian primary care settings remains limited. This study examined whether adding unripe papaya to the maternal diet improves breastfeeding smoothness among breastfeeding mothers in Sumedang Regency. Using a quantitative quasi-experimental design with a nonequivalent control group, 98 lactating mothers were recruited through purposive sampling and assigned to an intervention group, given 100 grams of unripe papaya per day for one week, or a control group (no treatment). Data were collected using a validated questionnaire and analyzed with the independent samples t-test. The intervention group had a mean breastfeeding smoothness score of 2.12, compared with 1.08 in the control group, a mean difference of 1.041 points (95% CI: 0.686 to 1.395; t = 5.831; p < 0.001). These results indicate that unripe papaya consumption improves breastfeeding smoothness in lactating mothers.